DEMOKRASI DAN NEGARA HUKUM DALAM ISLAM - Wahyuni, Sri (Jurnal Review Politik, 2012)
This article discusses the concept of democracy and the Islamic rule of law. Democracy is the supreme sovereignty of the people hands. On the other hand,  Islam is considered to theocracy, the highest of power is God's sovereignty. Both are different, but that there is an idea that  Islamology discourse ignores the contradictions between them, such as the concept of theo-democracy and concepts of Islam substantially. Both assume that Islam is relevant to democracy, such as tolerance, justice and equality. This ignores the formality of Islam, and does not emphasize a formal implementation of sharia. Islamic law (shari'a), can be implemented in a modern state, especially in Indonesia, by following the procedures in the legal system and modern law. The steps which being taken are the formulation, socialization and political stages.